The Relationship Between The Number of Children and The Distance of Pregnancy With The Nutritional Status of Toddlers In Lestari Dadi Village, Pegajahan District, Serdang Bedagai Regency Year 2022 - Yessy Arisman; Sri Hayanti (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Nutritional status plays an important role in determining the quality of human resources, especially children under five. Most people have the number of children under five in one family > 2 toddlers and not a few pregnancies are close together < 2 years. The distance of pregnancy and the number of children also affect the nutritional status of children under five. The research method used is analytic quantitative using a cross sectional design. The sample in this study used purposive sampling with a sample of 49 respondents and the data obtained in the study were analyzed through two stages, namely univariate to determine the description and bivariate to determine the relationship (chi square). The results showed that the number of children in the 2 category was 55.9%. The distance between pregnancies in the 2 year category was 83.7%. The nutritional status in the good nutrition category (Normal) was 69.4%. There is a relationship between the number of children and the nutritional status of children under five (p=0.043). There is a relationship between the distance of pregnancy with the nutritional status of children under five (p = 0.015). Based on the results of this study,the authors suggest to mothers who have toddlers to adjust the birth spacing and the number of toddlers owned so that the nutritional status of toddlers is good.